Character Education Management In Tawar Mojokerto Public Primary Schools - Kartiko, Ari; Rofiq, Ainur; Rokhman, Mauhibur; Kartika; Ritonga, Matnur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Character education must be instilled from an early age, considering that there has been a lot of violence in educational institutions recently. This research aims to find gaps with previous research by analyzing the school's vision and mission related to character education and secondly, knowing the implementation of character education in elementary schools which are the research locations. This research is qualitative research that uses a case study approach, where the data used is primary data and the source of information is the school principal, teachers and students at the school. The way to obtain data is through in-depth observation and interviews, while sample selection uses purposive sampling. Data analysis techniques use models in the form of data reduction, data presentation, drawing conclusions and verification. The research period was carried out from October to December 2023. The results of the research show that this character education focuses on affective aspects such as spiritual and social skills, which are not only integrated in subjects but are also supported by the P5 and PPRA programs. Budgeting for the implementation of character education is supported by several funding sources. The principal of SDN Tawar also assigns educators and education staff to delegate authority. Character education through intracurricular activities at SDN Tawar is integrated with all subjects, while self-development activities include counseling guidance, extracurricularmana activities and habituation